Elaeagnus latifolia Fruit Extract Ameliorates High-Fat Diet-Induced Obesity in Mice and Alleviates Macrophage-Induced Inflammation in Adipocytes In Vitro - Narongsuk Munkong; Nattanida Jantarach; Bhornprom Yoysungnoen; Piyanuch Lonan; Jiradej Makjaroen; Phorutai Pearngam; Sarinya Kumpunya; Kingkarnonk Ruxsanawet; Saharat Nanthawong; Poorichaya Somparn; Arthid Thim-Uam (Antioxidants)
Elaeagnus latifolia (EL) is a wild fruit known for containing several health-promoting compounds. This study aimed to evaluate the effects of EL fruit extract on high-fat diet (HFD)-induced obesity and lipopolysaccharide (LPS)-activated macrophages. Mice fed an HFD and given EL fruit extract for 10 weeks exhibited significantly lower body weight, reduced lipid accumulation, diminished oxidative stress in adipocytes, and decreased macrophage infiltration compared to those not receiving the EL extract. Moreover, the EL fruit extract activated the transcription factors Pparg and Cebpa, initiating adipogenesis and modulating the expression of NF-κB/Nrf-2-induced target genes. This resulted in smaller adipocyte size, reduced inflammation, and less oxidative stress in HFD-fed mice. In vitro, the EL extract induced a shift in macrophage phenotype from M1 to M2, reduced IκBα/NF-κB phosphorylation, and effectively decreased energy production in macrophages by downregulating the expression of several proteins involved in glycolysis and the tricarboxylic acid cycle. This mechanistic study suggests that administering EL fruit extract could be an effective strategy for managing obesity and its associated pathologies.